PERAN CITIZEN JOURNALISM DALAM PROGRAM BERITA STASIUN TELEVISI (STUDI DESKRIPTIF KUALITATIF TERHADAP SITUS LIPUTAN6.COM PADA PROGRAM BERITA LIPUTAN6 SCTV) - Fithryani, Nur (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2015)
Abstract:This research is a study to explore has about how is the role of citizen journalism in television news program especially about website Liputan6.com in the television news program Liputan6 SCTV. The purpose of this research is to know the role of citizen journalism in television news program Liputan6 SCTV that takes some news materials from the website Liputan6.com. This research used in depth-interview method with five informants. The theories that used in this research are diffusion of innovation theory. This theory is closely related to the innovation that made by Liputan6.com team. The next theory is new media theory that discuss about the development of new media nowadays.This research concluded that the role of citizen journalism in television news program is very important program but not to increase the rating or to gain the popularity.